The Recovery of Companies - EP CHEDLI, Mariem Kchaich (Journal of Economic Development, Environment and People, 2016)
The transmission of an enterprise faces different forms which are the recovery, indeed whether it’s about a sale or a succession the transmission often puts in danger the existence of an enterprise. An enterprise can be taken over by another enterprise as part of its external growth strategy or by an individual who can be an heir, a former employee of the enterprise, a commercial or financial partner or a foreign buyer for the firm, but whatever his prior knowledge of the target enterprise the individual buyer holds the position of a new manager and fits into a functioning structure and leads a staff that he did not recruit.. As part of our article, we have been interested in the study of the recovery of enterprises and its various aspects, in the first part the general case we discussed the resumption namely the transfer of businesses and through the brakes related to the transmission and the process of transmission. The second part is dedicated to the recovery and its integration in the fields of entrepreneurship, as well as the different forms that can take the recovery of a company namely: the external growth and the recovery of enterprises by individuals.